2015
DOI: 10.1002/2014ja020946
|View full text |Cite
|
Sign up to set email alerts
|

Localized polar cap flow enhancement tracing using airglow patches: Statistical properties, IMF dependence, and contribution to polar cap convection

Abstract: Recent radar observations have suggested that polar cap flows are highly structured and that localized flow enhancements can lead to nightside auroral disturbances. However, knowledge of these flows is limited to available echo regions. Utilizing wide spatial coverage by an all-sky imager at Resolute Bay and simultaneous Super Dual Auroral Radar Network measurements, we statistically determined properties of such flows and their interplanetary magnetic field (IMF) dependence. We found that narrow flow enhancem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 42 publications
3
40
0
Order By: Relevance
“…This speed underestimates the full E × B drift because the radar echoes here were from short‐range backscatter near the radar and were thus from the E region, where flow speed is limited to below the ion acoustic speed (~400 m/s) [ Haldoupis , ; Koustov et al ., ]. The width and speed of the flow agree with those identified by using radar observations only [ Nishimura et al ., ; Zou et al ., ], indicating that they are of the same phenomena identified with different approaches.…”
Section: Case Studiesmentioning
confidence: 87%
See 2 more Smart Citations
“…This speed underestimates the full E × B drift because the radar echoes here were from short‐range backscatter near the radar and were thus from the E region, where flow speed is limited to below the ion acoustic speed (~400 m/s) [ Haldoupis , ; Koustov et al ., ]. The width and speed of the flow agree with those identified by using radar observations only [ Nishimura et al ., ; Zou et al ., ], indicating that they are of the same phenomena identified with different approaches.…”
Section: Case Studiesmentioning
confidence: 87%
“…Although plasma motion in the polar cap is traditionally viewed as a large‐scale two‐cell pattern, mesoscale flow enhancements have been identified as a common feature based on recent radar observations [ Lyons et al ., ; Nishimura et al ., ; Zou et al ., ]. These flows are elongated in the noon‐midnight direction and are narrow in the dawn‐dusk direction, having a width of a few hundred kilometers as compared to the thousands of kilometers width of large‐scale convection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent ground‐based observations have shown that poleward boundary intensifications along the nightside auroral oval, which are considered as an ionospheric signature of magnetotail reconnection [ Zesta et al ., ], can be preceded by localized channels of enhanced flow in the polar cap. The channels have been identified in radar flow observations and optically via emissions from F region patches and auroral arcs [ Nishimura et al ., , ; Lyons et al ., ; Zou et al ., , ]. Such polar cap‐auroral connections suggest that some portion of magnetotail reconnection can be driven by localized inflows from the lobe to the plasma sheet and thus offer a possible explanation for why magnetotail reconnection and resulting plasma sheet flow channels/dipolarization fronts can be localized azimuthally.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, differences between large-scale convection patterns (SuperDARN) and smaller-scale plasma drift features (Swarm), especially around plasma density irregularities (e.g. Nishimura et al, 2014;Zou et al, 2015;Yang et al, 2015), are expected to result in a reduced correspondence between the two velocity estimates. Furthermore, Yang et al (2015, Fig.…”
Section: Swarm-superdarn Comparisonmentioning
confidence: 99%